Mindfulness Practices to Improve Achievement - Natalia, Karina; Utomo, Budi; Suherman, Heru (CV. Rayyan Dwi Bharata, 2024)
McClelland Wanless (2012) emphasize individuals' abilities to consciously regulate their thoughts, emotions, and behaviors, involving emotional and behavioral aspects. This research employs a literature study approach to delve into existing literature and summarize knowledge. A profound understanding of the interaction between procrastination, mindfulness, and self-regulation can provide a foundation for effective intervention strategies in higher education settings. The focus on developing self-regulation skills and enhancing mindfulness can be key steps in assisting students in overcoming procrastination and achieving optimal academic performance